Post office and the sustainability of triangle historical area in Semarang from the traditional era to the colonial era - Rukayah, Siti; Juwono, Sudarmawan; Etenia, Annica (Journal of Architecture and Urbanism, 2022)
Development of information and communication technology changed mail delivery services in various parts of the world in the twenty centuries. In Java, the increase in postal services as Dutch East Indies government infrastructure) grew along with the construction of the Postweg line (postal road) in 1809–1811. The road networks pass through Jakarta – Semarang, Surabaya, and another small-town facility and now the postal networks became a heritage. The networks of post building in Semarang are unique compared to other big cities in Java. The Dutch East Indies government anticipated the geography of Semarang when they developed the expansion of the town to the south and utilized it by postal services. The government has issued a cultural heritage regulation for buildings and areas, but has not touched the conservation network of heritage. Based on that problem, this paper aimed to reveal Semarang city pattern used post office and infrastructure as a tool for analysing city morphology and suggested to conserve the heritage network. The method used was urban design with the historical approach, the post office location, settlements, road networks, and geographic conditions. The research findings showed that the postal infrastructure formed the sustainability of Semarang city from local-Dutch Indies rule in triangle form. The city’s geographical factor also influenced the city’s layout. The local and colonial city character in this triangle area is still preserved, although some minor changes in the area postweg road. The sustainability city layout from the era of local government – the Dutch East Indies in Semarang by making the city centre of the local government (in the top of the triangle) as the centre of urban design should be input on the heritage regulation as areas conservation.